(untitled) (Música Hodie, 2019)
New England composer Stuart Saunders Smith (1948) is immersed in a milieu that echoes the American Transcendentalist movement. Transcendentalist figures, like Emerson and Thoreau, discussed notions also emphasized by Smith’s: autonomy, intuition, experience, self-reliance, self-actualization, pacifism, and a claim that each person is part of a single universal spirit—Oneness. This article focuses on how such notions reflect in Smith’s compositional process and how two particular aspects, pacifism and Oneness, reflect in the music that emerges from this process. In Smith’s compositional process, experience, “filtered” through intuition, is more important than pre-compositional systems. Therefore, his work is seen as antithetical to formalism. Oneness is achieved by leveling the roles of composer, performer, and audience. This procedure appears particularly in his trans-media systems, mobile compositions, and co-existence pieces. Pacifism emerges in his use of intricate rhythms. These stances suggest Smith’s music as part of a lineage of thought that traces back to the Transcendentalists: the idea of facing tradition critically while upholding free agency as the primary source of artistic creation.